As chuvas na região agreste da Borborema, nordeste do Brasil: proposta de setorização climática sob o enfoque da análise rítmica - Cavalcante, Gabriel de Paiva (2019)
The Brazilian Northeast Agreste is a region of important social, cultural and historical values. It is in this region that are located cities of urban centers essential for their respective states, such as Campina Grande, Paraíba, Caruaru, Pernambuco and Arapiraca, Alagoas state. In the specific case of Agreste da Borborema, the region of application of this study, we note the close relationship between the social and the natural, placing man as a producer agent in the region's lands, which sometimes occur with humid characteristics, sometimes with sertanejas features. which gives the region a particularity not seen in other portions of the northeastern geographical space. Agreste da Borborema is a region marked by landscape diversity that occurs over short distances, that is, as the issuing geographer Manuel Corrêa de Andrade points out, it is a miniature of the Northeast. In addition to landscape diversity, the natural aspects of the region are marked by the occurrence of the Borborema Plateau, the largest morphological domain in the region, which has influences on physical environmental systems, such as climate and, consequently, drainage. Perhaps because it has such natural diversity, so far little has been studied about the region, especially with regard to Regional Climatology. Thus, starting from the theoretical-methodological foundation of the Geographic Region and Climate Rhythm, which seeks to understand the usual and exceptional succession of types of weather and characterize the climate of the regions with emphasis on the regional atmospheric circulation, this paper aims to present a climatic sectorization for the Agreste region of Borborema by analyzing the participation of air masses and atmospheric systems and their effects on the genesis and variation of rainfall. In order to reach this objective, rain spatiotemporal analysis steps were performed in the Agreste region of Borborema, through the study of meteorological data on the time scale from 2005 to 2017, referring to 7 automatic stations, namely: Santa Cruz / RN , Areia / PB, Campina Grande / PB, Surubim / PE, Caruaru / PE, Garanhuns / PE and Palmeira dos Indios / AL. The election of the standard years was performed through the variation of rainfall, using the quantile technique. 2011 was classified as the Very Rainy Standard Year, 2013 as the Normal Standard Year, and 2012 as the Very Dry Standard Year. Based on the results obtained by analyzing the rhythm of climatic attributes during the standard years, as well as the temporality and spatiality of atmospheric systems and air masses, the Agreste de Borborema region was divided into two sectors with different characteristics. Regarding the genesis of the rains: Northern Agreste sector, which includes the Santa Cruz / RN, Areia / PB and Campina Grande / PB stations, marked by rainfall production through the East Waves and the Intertropical Convergence Zone ; and Southern Agreste sector, composed by the Surubim / PE, Caruaru / PE, Garanhuns / PE and Palmeira dos Índios / AL stations, and whose main climatic characteristic is the predominance of the Atlantic Equatorial Mass, with less significant occurrences of the Waves. of the East and the Cold Front Repercussions, the last one that acts more incisively in the Alagoas Palmeira dos Índios station. As a perspective for future studies in the field of Regional Climatology, it is expected that the methodological issue will be improved with the use of technological resources and climate modeling, as there is a considerable limitation regarding the climate attributes data.